Transformações no acesso à informação: o papel da Biblioteca Central da Universidade de Caxias do Sul para o letramento informacional - Baptista, Michele Marques (My University, 2025)
The COVID-19 pandemic, declared in March 2020 by the World Health Organization (WHO), brought about profound transformations in the global educational landscape, directly impacting educational processes and the operation of university libraries. With the suspension of in-person activities in educational institutions, it became urgent to adapt services and resources to the digital environment, ensuring access to information, reading, and support for the academic community. In this context, this research aimed to analyze information literacy, informational practices, and user behavior at the Central Library of the University of Caxias do Sul (BICE/UCS), considering the pre-pandemic, pandemic, and post-pandemic periods, with the goal of proposing improvements and innovations in the products, services, and technologies offered. The investigation, exploratory in nature and based on a qualitative approach, adopted three main sources of evidence: (i) analysis of statistical reports from the library management system (Pergamum) and from the digital platforms contracted by the institution; (ii) application of an online questionnaire to the academic community (students, faculty, and administrative staff); and (iii) conduction of Focus Groups with library users, seeking to deepen the understanding of their perceptions and experiences during the period of social isolation and after the gradual return to in-person activities. The theoretical framework is grounded in concepts such as information literacy, informational competencies, information behavior, information mediation, academic reading, and the strategic role of university libraries in contemporary educational processes. The results support the thesis that BICE functions as a mediator of information access and a promoter of information literacy, adjusting its strategies to the changes observed in users? informational behavior during and after the pandemic. They also reveal that, in response to the restricted access to the physical collection, BICE implemented several innovations to maintain its institutional relevance. The study shows that users? informational behavior was significantly affected by the pandemic, requiring the development of new competencies for the critical, ethical, and efficient use of digital information. Information and reading competencies proved essential in fostering users' autonomy in searching for, selecting, and using reliable information. Furthermore, the analysis of patterns in the use of informational resources over the three periods enabled the formulation of strategies better aligned with the academic community?s needs and the transformations in educational processes. Among the study's contributions, the importance of continuous evaluation of library services stands out as a tool to support decision-making, strategic planning, and the formulation of collection development policies. The role of the librarian is also reinforced as an active mediator in the formation of critical and autonomous readers, integrating innovative educational and technological actions. In doing so, this thesis contributes to advancing knowledge by demonstrating how university libraries can respond effectively to crisis scenarios, maintaining their status as essential spaces for access to reading, knowledge, digital inclusion, academic development, and social advancement. The experience of BICE/UCS during and after the pandemic serves as a significant example of adaptation, innovation, and commitment to its institutional mission of supporting teaching, research, and community outreach. [resumo fornecido pelo autor]
A pandemia da COVID-19, declarada em março de 2020 pela Organização Mundial da Saúde (OMS), provocou profundas transformações no cenário educacional global, impactando diretamente os processos educacionais e o funcionamento das bibliotecas universitárias. Com a suspensão das atividades presenciais nas instituições de ensino, tornou-se urgente adaptar serviços e recursos ao ambiente digital, assegurando o acesso à informação, à leitura e ao suporte à comunidade acadêmica. Nesse contexto, esta pesquisa teve como objetivo analisar o letramento informacional, as práticas informacionais e o comportamento dos usuários da Biblioteca Central da Universidade de Caxias do Sul (BICE/UCS), considerando os períodos pré-pandêmico, pandêmico e pós-pandêmico, com vistas à proposição de melhorias e inovações nos produtos, serviços e tecnologias ofertados. A investigação, de caráter exploratório e abordagem qualitativa, adotou três fontes principais de evidências: (i) análise dos relatórios estatísticos do sistema de gerenciamento da biblioteca (Pergamum) e das plataformas digitais contratadas pela instituição; (ii) aplicação de questionário on-line à comunidade acadêmica (discentes, docentes e técnicos administrativos); e (iii) realização de Grupos Focais com usuários da biblioteca, buscando aprofundar as percepções e experiências vivenciadas durante o período de isolamento social e após o retorno gradual às atividades presenciais. O referencial teórico apoia-se em conceitos como letramento informacional, competências informacionais, comportamento informacional, mediação da informação, leitura acadêmica e o papel estratégico das bibliotecas universitárias nos processos educacionais contemporâneos. Os resultados comprovam a tese de que a BICE atua como mediadora do acesso à informação e promotora do letramento informacional, ajustando suas estratégias às mudanças observadas no comportamento informacional dos usuários durante e após a pandemia. Também revelam que, diante das restrições de acesso ao acervo físico, a BICE implementou diversas inovações para manter sua relevância institucional. O estudo evidencia que o comportamento informacional dos usuários foi significativamente impactado pela pandemia, exigindo o desenvolvimento de novas competências para o uso crítico, ético e eficiente da informação em meio digital. As competências informacionais e leitoras mostraram-se essenciais para promover a autonomia dos sujeitos na busca, seleção e utilização de informações confiáveis. Além disso, a análise dos padrões de uso dos recursos informacionais ao longo dos três períodos possibilitou o delineamento de estratégias mais alinhadas às necessidades da comunidade acadêmica e às transformações nos processos educacionais. Dentre as contribuições do estudo, destaca-se a importância da avaliação contínua dos serviços da biblioteca como instrumento de apoio à tomada de decisões, planejamento estratégico e formulação de políticas de desenvolvimento de coleções. Reforça-se, ainda, o papel do bibliotecário como mediador ativo na formação de leitores críticos e autônomos, articulando ações educativas e tecnológicas inovadoras. Com isso, esta tese contribui para o avanço do conhecimento ao demonstrar como as bibliotecas universitárias podem responder de forma eficaz a cenários de crise, mantendo-se como espaços fundamentais de acesso à leitura, ao conhecimento, à inclusão digital, à formação acadêmica e ao desenvolvimento social. A experiência da BICE/UCS durante e após a pandemia constitui um exemplo significativo de adaptação, inovação e compromisso com a missão institucional de apoio ao ensino, à pesquisa e à extensão. [resumo fornecido pelo autor]
Keywords: Universidade de Caxias do Sul. Sistema de Bibliotecas. Biblioteca Central; Letramento informacional; Ciência da informação; Bibliotecas - Estudo de usuários; COVID-19.; Serviços de informação; University of Caxias do Sul. Library System. Central Library.; Information literacy; Information science; Libraries - Use studies; COVID-19; Information services